#177 Microwave-assisted synthesis of surface passivated fluorescent carbon nanodots from Buchnanialanzan leaves extract - Jana, Pradip; Dev, Abhimanyu (Journal of Pharmaceutical Chemistry, 2022)
The current work is designed to synthesize fluorescent carbon nanodots (CDs) by microwave treatment of Buchnania lanzan leaves extract. The methanolic extract of Buchnania lanzan leaves serves as the carbon precursor for CDs synthesis. Leaves extract was initially treated in a microwave oven, and the residue obtained was cooled at room temperature, and then it was reconstituted with polyethylene glycol 4000 (PEG 4000) solution. The obtained solution was again treated in a microwave oven, and the residue was cooled and reconstituted with Milli-Q. Here, PEG 4000 acts as a surface passivating agent. Afterward, the brown-colored passivated CDs (CDPs) solution was centrifuged, and the supernatant was filtered through a syringe filter to remove dark carbonaceous matters and to get pure CDPs. Finally, CDPs solution was lyophilized in order to obtain CDPs in powder form. The synthesized CDPs were studied by several characterization techniques like- UV-visible spectroscopy, Fluorescence spectroscopy, Fourier transform infrared (FTIR) spectroscopy, and zeta potential. The as-prepared CDPs solution was of brown color in daylight while it exhibited green fluorescence under UV light. The UV-visible spectrum of CDPs showed a sharp peak at 282.50 nm and a shoulder peak at about 350 nm, which is in accordance with earlier reports. CDPs exhibited an excitation-dependent emission behavior in the fluorescence spectrum, which is a distinct characteristic of CDs. FTIR spectrum of CDPs suggested the presence of carboxyl, amino surface functional groups, and aromatic C=C bonds. Further, the negative zeta potential of -9.77 mV supports the FTIR data, indicating CDPs surface rich in carboxyl functionality. As in this study, a simple and cost-effective synthesis of fluorescent CDPs from a renewable and abundant plant source is carried out; this method could offer a large-scale synthesis of carbon nanodots for the applications in the fields of drug delivery bioimaging, photocatalysts, biosensors, etc.